Comparison of methods for the enumeration of enterohemorrhagic Escherichia coli from veal hides and carcasses - Luedtke, Brandon E.; Bosilevac, Joseph M. (Frontiers in Microbiology, 2015)
The increased association of enterohemorrhagic Escherichia coli (EHEC) with veal calves has led the United States Department of Agriculture Food Safety and Inspection Service to report results of veal meat contaminated with the Top 7 serogroups separately from beef cattle. However, detection methods that can also provide concentration for determining the prevalence and abundance of EHEC associated with veal are lacking. Here we compared the ability of qPCR and a molecular based most probable number assay (MPN) to detect and enumerate EHEC from veal hides at the abattoir and the resulting pre-intervention carcasses. In addition, digital PCR (dPCR) was used to analyze select samples. The qPCR assay was able to enumerate total EHEC in 32% of the hide samples with a range of approximately 34 to 91,412 CFUs/100 cm2 (95% CI 4-113,460 CFUs/100 cm2). Using the MPN assay, total EHEC was enumerable in 48% of the hide samples and ranged from approximately 1 to greater than 17,022 CFUs/100 cm2 (95% CI 0.4-72,000 CFUs/100 cm2). The carcass samples had lower amounts of EHEC with a range of approximately 4 to 275 CFUs/100 cm2 (95% CI 3-953 CFUs/100 cm2) from 17% of samples with an enumerable amount of EHEC by qPCR. For the MPN assay, the carcass samples ranged from 0.1 to 1 CFUs/100 cm2 (95% CI 0.02-4 CFUs/100 cm2) from 29% of the samples. The correlation coefficient between the qPCR and MPN enumeration methods indicated a moderate relation (R2=0.39) for the hide samples while the carcass samples had no relation (R2=0.002), which was likely due to most samples having an amount of total EHEC below the reliable limit of quantification for qPCR. Interestingly, after enrichment, 81% of the hide samples and 94% of the carcass samples had a detectable amount of total EHEC by qPCR. From our analysis, the MPN assay provided a higher percentage of enumerable hide and carcass samples, however determining an appropriate dilution range and the limited throughput offer additional challenges.